The struggle over the criminal jury an echoed debate in Latin America - Ramos Núñez, Carlos (2018)
In the present article, the author analyzes the positions for and against the juridical institution of the criminal jury, which would inﬂuence Latin America in the second half of the 19th century and the ﬁrst decades of the 20th century.This is done by exposing the opinions expressed by European and Latin American authors whose ideas were characterized by extremely varied legal and political connotations and, sometimes, completely opposed to one another. Likewise, the historical background that characterizes each of the countries from which the authors mark their positions is presented.